2007
DOI: 10.1111/j.1600-6143.2007.01796.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunity, Homing and Efficacy of Allogeneic Adoptive Immunotherapy for Posttransplant Lymphoproliferative Disorders

Abstract: Adoptive immunotherapy using autologous EpsteinBarr virus (EBV)-specific cytotoxic T-lymphocytes (auto-CTL) can regress posttransplant lymphoproliferative disorders (PTLD). Widespread applicability of auto-CTL remains constrained. Generation is timeconsuming, and auto-CTL cannot be established in patients treated with the B-cell depleting antibody rituximab. By contrast, pregenerated allogeneic CTL (allo-CTL) offers immediate accessibility. Allo-CTL has previously shown efficacy in "early" polyclonal-PTLD. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 22 publications
3
38
0
Order By: Relevance
“…However, restoring immunity alone may be insufficient, and the risk of graft rejection calls for careful consideration of all available therapies. Complementary interventions include infusing donor lymphocytes (typical healthy donor mononuclear cells are comprised of about 5% EBV-directed cells) (17), infusing EBV-specific cytotoxic T cells that are grown ex vivo by exposing HLA-matched T cells to EBV antigens (37,64,79,85,168), and infusing anti-CD20 monoclonal antibody (e.g., rituximab) (33,60,71,72,171,197). If initial intervention is insufficient, more traditional cancer treatment with radiation and multidrug chemotherapy is used (135,190).…”
Section: Assessing Therapeutic Efficacymentioning
confidence: 99%
“…However, restoring immunity alone may be insufficient, and the risk of graft rejection calls for careful consideration of all available therapies. Complementary interventions include infusing donor lymphocytes (typical healthy donor mononuclear cells are comprised of about 5% EBV-directed cells) (17), infusing EBV-specific cytotoxic T cells that are grown ex vivo by exposing HLA-matched T cells to EBV antigens (37,64,79,85,168), and infusing anti-CD20 monoclonal antibody (e.g., rituximab) (33,60,71,72,171,197). If initial intervention is insufficient, more traditional cancer treatment with radiation and multidrug chemotherapy is used (135,190).…”
Section: Assessing Therapeutic Efficacymentioning
confidence: 99%
“…Of note, no patient developed graft-versus-host disease post-CTL administration. Similar positive outcomes were reported in two solid-organ recipients with CNS lymphoma who received closely matched EBV-specific T cells resulting in complete resolution of their brain lesions [21]. Based on this promising data, we recently initiated a Phase I multicenter trial to evaluate banked trivirusspecific CTLs into third-party HSCT recipients with encouraging early clinical results in five out of eight evaluable recipients with serious viral disease.…”
Section: Third-party Banksmentioning
confidence: 62%
“…Theoretically, a decrease in viral load suggests a decrease in tumor burden; however, if samples are taken immediately after treatment, it is plausible that the EBV DNA load will spike as tumor cells apoptose. For instance, we observed that EBV DNA viral load significantly increased in patients with PTLD immediately postadoptive T-cell therapy and then returned to undetectable levels prior to subsequent infusions [15]. The kinetics of EBV DNA viral load is unknown, and a more thorough understanding is required.…”
mentioning
confidence: 97%